PENGEMBANGAN KONTEN MATERI PEMBELAJARAN SENI BERBASIS NILAI-NILAI RELIGIUS - Febriana Ekananda Suras; Pamungkas, Joko (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2024)
This research aims to describe how religious values are taught to children. This research focuses on analyzing the implementation of learning that is used to instill religious values in children. This research uses a qualitative approach to describe a phenomenon obtained in depth based on field conditions. This type of research uses descriptive analysis to describe the content of artistic learning used. The subjects of this study were 18 children aged 4-6 years and the director and 2 teachers in Sari Mekar Kindergarten, Banguntapan, Bantul, Yogyakarta. Data were collected using interview and observation techniques. Data analysis was done using the Miles & Huberman method, namely data collection, data reduction, and data presentation. The results of this study indicate that learning art based on religious values in early childhood through coloring ogoh-ogoh pictures and making simple ogoh-ogo replicas can provide an understanding of religion, tradition, and gratitude to God through material content related to ogoh-ogoh parade on Nyepi day.